A study on movement characteristics and distribution law of dust particles in open-pit coal mine - Tong Wu (Nature Portfolio, 2021)
Abstract Previous simulation studies of dust particles movement behavior in open-pit coal mines only aimed at a single operation link, and the macro simulation is lacking. This study seeks to explore microscopic migration and macroscopic diffusion of dust particles in the mining area by numerical simulation method. The movement characteristics revealed, and the distribution law of the dust particles in a stable state with the corresponding migration paths in the mining area were obtained respectively. The results showed that the increase amplitude of dust particles diffusion velocity was inversely proportional to particle size, which was vital for dust pollution in the mine. And the larger the particle size in the mining pit was, the lower the escape rate of the dust particles was. Dust particles distributed over a wide range that were not limited by space height, and the distribution characteristics of dust particles at different heights were basically the same. Meanwhile, it is found that the dust distribution in the two places is relatively concentrated due to the circulation phenomenon of the mining pit and the west dump. And wind action would accelerate the moving dust particles to reach a stable distribution state.